(untitled) (Journal of Science and Technology, 2016)
This work involved the measurement of fasting blood glucose (FBG) and glycosylated haemoglobin (HbA1c) levels of diabetes mellitus patients as an index of glycaemic control. It was a prospective casefinding study using laboratory and general practice records. The subjects were confirmed diabetic patients, attending a Diabetic Clinic at the Komfo Anokye Teaching Hospital, Kumasi, Ghana. The fasting blood glucose levels were measured in millimolar concentration and corrected glycosylated haemoglobin (HbA1c) levels expressed as percentages. The mean level of fasting blood glucose (± standard deviation) for the non-diabetics was 4.91 ± 1.08 mmol/L and the corresponding mean value for the HbA1c was 5.40 ± 0.84%. There was a linear correlation between the fasting blood glucose and HbA1c. Out of the 99 diabetics, 9 of them had near-normal levels of HbA1cwhile 64 had mean values between 12 and 16%. There was generally high levels of glycosylated haemoglobin in the majority of patients studied, reflecting their poor glycaemic control. This suggests a relatively large proportion of the diabetics could be predisposed to microvascular complications, while a small group with near-normal HbA1c levels could be prone to hypoglycaemic complications.